A VISUAL MEMBRANE IMMUNOASSAY FOR THE DETECTION OF METHAMPHETAMINE USING AN ENZYME-LABELED TRACER DERIVED FROM METHAMPHETAMINE AND AMPHETAMINE - CHOI, MJ; GOROVITS, BM; CHOI, J; SONG, EY; NAM, KS; PARK, J (PHARMACEUTICAL SOC JAPAN, 1994)
A visual membrane enzyme immunoassay is described for the measurement of methamphetamine in urine. To increase assay sensitivity, tracers with chemically similar structures were cross-checked with the antibodies to determine their influence on the antibody binding. Tracers of horseradish peroxidase-labeled methamphetamine (MA-HRP) and amphetamine (A-HRP) derivatives were prepared for this purpose. Significant differences in antibody specificity were found between the two tracers. Based on the results of this study, a pair of an antibody and a tracer was selected and a membrane enzyme immunoassay (EIA) was developed utilizing the competitive binding between methamphetamine and the drug-HRP tracer. UltraBind membrane (0.45 mum) was used as the solid matrix to which the antibody was attached. Using diaminobenzidine substrate with Co2+ ion, a stable grey color appeared on the surface of membrane for MA-negative urine samples. No color appeared for MA-positive urine with a cut-off level of 0.8 ppm.
Keywords: REAGENT POLARIZATION FLUOROIMMUNOASSAY; URINE